Comparative Analysis of Twenty Master’s Education Programs in Colombia (2016)
Education is one of the main pillars to achieve social goals, such as reducing poverty and improving quality of life. In this sense, teachers become one of the most important gears in the educational system and therefore it is necessary to evaluate various qualitative and quantitative variables that allow them to choose a master program that meets their expectations. This research is intended as a guide for comparing the logistical aspects (such as location, modality and price), and academic aspects (such as research approaches and concentration areas of study, curriculum and degree requirements) among twenty Colombian universities, both public and private, that offer master degrees in education.